Non-parent of Origin Expression of Numerous Effector Genes Indicates a Role of Gene Regulation in Host Adaption of the Hybrid Triticale Powdery Mildew Pathogen - Praz, Coraline R.; Menardo, Fabrizio; Robinson, Mark D.; Müller, Marion C.; Wicker, Thomas; Bourras, Salim; Keller, Beat (Frontiers in Plant Science, 2018)
Powdery mildew is an important disease of cereals. It is caused by one species, Blumeria graminis, which is divided into formae speciales each of which is highly specialized to one host. Recently, a new form capable of growing on triticale (B.g. triticale) has emerged through hybridization between wheat and rye mildews (B.g. tritici and B.g. secalis, respectively). In this work, we used RNA sequencing to study the molecular basis of host adaptation in B.g. triticale. We analyzed gene expression in seven virulent isolates of wheat, rye, and triticale mildews and identified a core set of effector genes that are highly expressed in all formae speciales. We also found that the genes differentially expressed between isolates of the same form as well as between different formae speciales were enriched in putative effectors. Their coding genes belong to several families including some which contain known members of mildew avirulence (Avr) and suppressor (Svr) genes. Based on these findings we propose that effectors play an important role in host adaptation that is mechanistically based on Avr-Resistance gene-Svr interactions. We also found that gene expression in the B.g. triticale hybrid is mostly conserved with the parent-of-origin, but some genes inherited from B.g. tritici showed a B.g. secalis-like expression. Finally, we identified 11 unambiguous cases of effector genes with hybrid-specific, non parent-of-origin gene expression, and we propose that they are possible determinants of host specialization in triticale mildew. These data suggest that altered expression of multiple effector genes, in particular Avr and Svr related factors, might play a role in mildew host adaptation based on hybridization.